Influence of composite resin volume and C-factor on the polymerization shrinkage stress - Mondelli, Rafael Francisco Lia; Velo, Marilia Mattar de Amoêdo Campos; Gonçalves, Rafael Simões; Tostes, Bhenya Ottoni; Ishikiriama, Sergio Kiyoshi; Bombonatti, Juliana Fraga (Brazilian Dental Science, 2016)
Objective: Composite polymerization shrinkage stress is an inherent process of chemical and light composite resin activation. Consequently, this fact has been associated to potential clinical problems. The aim of the present in vitro study was to evaluate the volume and C-factor influence on chemical and lightcuring composite resin polymerization shrinkage stress, using a non-rigid method that thereby provides lower stress values, causing a minimal deflection in load cell. Materials and Methods: The contraction forces of the Z-250 and Concise composite resins during polymerization were recorded in an UTM in two experiments. In the first experiment, the Z-250 composite was inserted beetwen two rectangular steel plates (6.0 x 2.0 mm), varyng the resin volumes and C-factors, in a single increment, polymerized for 20 s and the forces generated were recorded for 120 s. In the second experiment, a pair of rectangular steel plates (3x2mm) and two square steel plates (2x2mm), with varied heights (2; 3 mm, respectively), were used to determine the C-factor (0.6; 0.3) influence. Results: The polymerized Z-250 results showed that the volume variations, independent of the C-factor, had a direct influence on the shrinkage stress, different from the Concise, which was influenced by the C-factor. Conclusion: The present study showed that a higher volume of composite resins determines an increase in the shrinkage stress of light-curing composites. Keywords C-factor. Composite resin. Polymerization. Shrinkage stress.